VALUATION STUDY OF BBCA, BMRI, AND BBNI SHARES BASED ON PRICE TO EARNINGS RATIO (PER) AND PRICE TO BOOK VALUE (PBV) APPROACHES FOR THE 2020-2024 PERIOD - Muniroh, Muniroh; Zuchroh, Imama (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
This study aims to analyze the stock valuation of PT Bank Central Asia Tbk (BBCA), PT Bank Mandiri Tbk (BMRI), and PT Bank Negara Indonesia Tbk (BBNI) based on the Price to Earnings Ratio (PER) and Price to Book Value (PBV) methods in the 2020-2024 period. This study uses a quantitative descriptive method, which aims to provide an overview of stock valuation by comparing the PER and PBV of each company against the average banking sector. The analysis results show that BBCA shares tend to be overvalued based on PER in 2020, 2022, and 2023, while in 2021 and 2024 they are undervalued. BMRI shares show a more volatile pattern with a tendency to be undervalued in 2021, 2023, and 2024, and overvalued in 2020 and 2022. BBNI shares are more often in an overvalued condition, especially in 2020, 2022, 2023, and 2024, with the exception of 2021 which is classified as undervalued. Based on PBV, BBCA shares were consistently overvalued throughout the study period, reflecting investors' high expectations of the company's performance and prospects. In contrast, BMRI and BBNI stocks are more often undervalued, which indicates investment potential for investors with a value investing strategy. This research provides implications for investors in making investment decisions in the banking sector by considering stock valuation analysis. In addition, this research can be a reference for the development of stock valuation studies with broader methods, such as Discounted Cash Flow (DCF) or EV/EBITDA, to obtain more comprehensive results.